Scaling up climate services for farmers: Mission Possible. Learning from good practice in Africa and South Asia - Tall, Arame; Hansen, James; Jay, Alexa; Campbell, Bruce M.; Kinyangi, James; Aggarwal, Pramod K.; Zougmoré, Robert B. (2014)
This report presents lessons learned from 18 case studies across Africa and South Asia that have developed and delivered weather and climate information and related advisory services for smallholder farmers. The case studies and resulting lessons provide insights on what will be needed to build effective national systems for the production, delivery, communication and evaluation of operational climate services for smallholder farmers across the developing world. The case studies include two national-scale programmes that have been the subject of recent assessments: India’s Integrated Agrometeorological Advisory Service (AAS) Program, which provides tailored weather-based agrometeorological advisories to millions of farmers; and Mali’s Projet d’Assistance Agro-meteorologique au Monde Rural, which provided innovative seasonal agrometeorological advisory services for smallholder farmers and 16 less mature initiatives operating at a pilot scale across Africa and South Asia. The case studies were examined from the standpoint of how they address five key challenges for scaling up effective climate services for farmers: salience, access, legitimacy, equity and integration.